Myelin oligodendrocyte glycoprotein antibody-associated disease: A central nervous system demyelinating disorder – Case report - Parab, Shraddha Mahadev; Gawade, Sanika Sanjay; Dharne, Ankita Raghunath; Jadhav, Shruti Dinesh; Chavan, Sakshi Rajan; Gawade, Kirti Satish; Oak, Tejas Pravin; Jagtap, Vijay Arjun (Indian Journal of Case Reports, 2025)
MOGAD, or Myelin Oligodendrocyte Glycoprotein Antibody-associated Disease, is a less-known demyelinating disease that causes inflammation to the CNS (central nervous system) and has been known for a few recent years. It is observed to be in close association with many other neuroinflammatory diseases and is now recognized as a separate condition from Multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD). The disease's pathophysiology, treatment, and outlook differ from those for MS or NMOSD, which are concerned with aquaporin-4 antibodies. This study aims to get acquainted with the etiology, clinical manifestations, pathophysiology, epidemiology, diagnosis, and treatment of MOGAD. The study also involves a recent case study of MOGAD. The present study traversed a wide range of literature reviews by referring to articles published in international journals and available on internet sources like Google Scholar and PubMed. The case study refers to a female patient (age: 20 years) with a complaint of right eye vision blurring gradually progressive with mild right eye pain, who was subsequently diagnosed positive for MOGAD. There was no significant medical history, drug history, or medical history related to MOGAD. Treatment of attacks with corticosteroids was the first-line treatment, which was followed by preventive therapy with monoclonal antibodies, Rituximab in biannual cycles. This case study is presented to throw light on a rare disease like MOGAD and encourage further research related to the same.